RANCANG BANGUN WEBSITE PENGENALAN PROFIL SEKOLAH MADRASAH IBTIDAIYAH QURROTA A’YUN NGLOROG - Hafid Ardi Fatkhurrohman (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Madrasah Ibtidaiyah (MI) Qurrota a'yun which is located on JL. Ngrandu, Nglorog, Kec. Sragen, Sragen Regency, Central Java Province. One of the madrasas who delivered was still using brochures and invitations. The brochure contains profiles, achievements, extra-curricular activities, registration paths, fees, and facilities. Websites that are made responsively to facilitate access through several platforms. Methods in making responsive websites using Bootstrap as a CSS framework. The expected results are responsive websites for admins and madrasa profile visitors using an easily accessible platform. On the website there is a page that displays the homepage, school profile, achievements, teachers, and facilities. The items on the web page have functions and information. The end result of this research is a web system that has a function in storing or disseminating school information and as a medium of introduction or promotion to attract the wider community. Based on black box and SUS testing, the results show that the system can run well with a score of 75.25, which means the system is acceptable and feasible to use.